NMR study of gallosilicate natrolite - Sapiga, A.A.; Olszewski, M.; Paczwa, M.; Sapiga, A.V.; Sergeev, N.A. (Functional Materials, 2014)
Solid-state ²⁹Si, ²⁷Al and ⁷¹Ga NMR MAS spectroscopy was used to study the natural mineral - natrolite (Na₁₆Al₁₆Si₂₄O₈₀⋅ 16H₂O) and gallosilicate Na₁₆Al₁₆Si₂₄O₈₀⋅ 16H₂O (Ga-natrolite). It has been shown that these natrolites form have sufficiently well-ordered structure also and contain Si(MO₄)₃(SiO₄) and Si(MO₄)₂(SiO₄)₂ (where M = Al or Ga) structural units mainly. Our ⁷¹Ga NMR MAS results indicate that in Ga-natrolite there are at least two different Ga cations with ratio (10:1).